2016
DOI: 10.1155/2016/1262017
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photocatalytic Performance of MWCNTs/TiO2Nanocomposites for Degradation of Aqueous Substrate

Abstract: In this study, multiwalled carbon nanotubes (MWCNTs)/TiO 2 nanocomposites were obtained by constant volumetric wet impregnation processes. The prepared catalysts were characterized by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The effect of reaction conditions on photocatalytic performance of the catalysts was investigated by the degradation of methyl orange (MO) under UV irradiation, in a new type of reactor with unique structure. The results showed that the prepared nanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Park et al decorated titania on aerogel of SWCNTs and successfully applied for the removal of methylene blue from water [86]. Zhao et al fabricated MWCNTs-TiO 2 and applied for the photodegradation of methylene blue [87]. Xu et al designed photocatalysts by the combination of hydroxy-MWCNTs and PbO 2 nanocrystalline anode and applied it successfully for the removal of pyridine from water [88].…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…Park et al decorated titania on aerogel of SWCNTs and successfully applied for the removal of methylene blue from water [86]. Zhao et al fabricated MWCNTs-TiO 2 and applied for the photodegradation of methylene blue [87]. Xu et al designed photocatalysts by the combination of hydroxy-MWCNTs and PbO 2 nanocrystalline anode and applied it successfully for the removal of pyridine from water [88].…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…The photo-catalytic performance of these composites was tested for the degradation of methyl orange (MO). The results indicated that modified nanocomposites exhibited higher MO degradation efficiency than the pure nano-TiO 2 (Duan et al 2016).…”
Section: Applications Of Titania-doped Multi-walled Carbon Nanotubesmentioning
confidence: 97%
“…MWCNTs as adsorption media have significantly achieved great attention because of their excellent hydrocarbon removal capacities following the surface functionalization as detailed by Kim et al (2012) similarly for the reduction of dyes as studied by Duan et al (2016). MWCNTs-based adsorbents have been widely explored for the removal of heavy metals from industrial effluents and have shown high sorption performance among all known adsorbents.…”
Section: Applications Of Multi-walled Carbon Nanotubes In Oil Spills and Organic Hydrocarbons Removalmentioning
confidence: 99%
See 2 more Smart Citations